Investigation of structural, electrical and photoresponse properties of composite based Al/NiO:CdO/p-Si/Al photodiodes - Gurgenc, Ezgi; Dikici, Aydin; Aslan, Fehmi (Elsevier, 2022)
In the present study, different molar ratios of (1:0, 0:1, 3:1, 1:1, and 1:3) NiO:CdO composite thin films were coated on p-Si by a dynamic sol-gel spin coating method. Structural characterizations of NiO:CdO thin films were performed by XRD, FE-SEM, and EDX analysis. The photoresponse and electrical behavior of the fabricated photodiodes were determined by current-voltage (I-V), transient photocurrent-time (I-t), capacitance-voltage (C-V), conductivity-voltage (G-V), and transient photocapacitance-time (C-t) measurements. All fabricated photodiodes were exhibited rectifying properties and the photocurrent values increased as the light intensity was increased. All photodiodes are sensitive to light and it was determined that the NiO photodiode exhibited the highest photosensitivity value. Photocapacitance and photoconductance values of photodiodes were affected by light. Photoresponse and electrical behavior were affected by the interface states and the NiO:CdO ratio. The results show that Al/NiO:CdO/p-Si/Al photodiodes can be used as photosensors or photocapacitors in optoelectronic applications.
Keywords: Composite photodiode; Thin film; Nanomaterial; Photoresponse; Solar irradiation